2021
DOI: 10.21037/tau-20-1228
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function in the penile cancer survivor: a narrative review

Abstract: Squamous cell carcinoma of the penis is a rare malignancy among men in North America and Europe with an incidence of <1 per 100,00 men. Of all genitourinary cancers, penile carcinoma has the potential to jeopardize sexual function the most. The treatment modalities of penile carcinoma span the gamut from organ-sparing treatments such as topical therapy, laser therapy, radiotherapy, glansectomy, widelocal excision and partial or total penectomy. There is a relative paucity of data in the medical literature desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…The treatment modalities of PEC depend on the area involved and include some organ-sparing treatments such as topical therapy, laser therapy, RT, glansectomy, wide-local excision, and partial penectomy. Total penectomy is reserved for cases with more advanced primary disease ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…The treatment modalities of PEC depend on the area involved and include some organ-sparing treatments such as topical therapy, laser therapy, RT, glansectomy, wide-local excision, and partial penectomy. Total penectomy is reserved for cases with more advanced primary disease ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the QoL level of PC patients are driven to a significant extent by PC treatment modalities, and the burden of psychiatric symptoms increases with a more aggressive treatment approach [21]. This leads to alterations in sexual functioning as well as changes in patients' body image and perception of their sexuality [22][23][24][25]. In a study conducted by Opjordsmoen et al, some PC patients reported that if it was possible, they would rather choose to live shorter after treatment but with more preserved sexual function [26].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, most studies relied upon the IIEF questionnaire to evaluate the pre- to post-partial penectomy change in sexual function. This questionnaire has been criticised because it does not provide information on sexual stimulation via non-penetrative means or self-stimulation [ 47 ], and provides limited information on psychosexual background and partner relationship [ 9 ]. Future studies using a range of questionnaires which capture different aspects of sexual function pre- and post-partial penectomy are therefore warranted.…”
Section: Discussionmentioning
confidence: 99%